2016
DOI: 10.1136/bmjgh-2016-000105
|View full text |Cite
|
Sign up to set email alerts
|

Controlling cardiovascular diseases in low and middle income countries by placing proof in pragmatism

Abstract: Low and middle income countries (LMICs) bear a huge, disproportionate and growing burden of cardiovascular disease (CVD) which constitutes a threat to development. Efforts to tackle the global burden of CVD must therefore emphasise effective control in LMICs by addressing the challenge of scarce resources and lack of pragmatic guidelines for CVD prevention, treatment and rehabilitation. To address these gaps, in this analysis article, we present an implementation cycle for developing, contextualising, communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 23 publications
1
60
0
Order By: Relevance
“…Without targeted contextualized (13) and appropriately communicated guidelines, care providers, patients, policy makers, payers, and communities are not guided adequately on the best practices to yield better outcomes (13). Considerations for contextualization should include factors related to each of the stakeholders, including external contextual factors (policies, incentivization structures, dominant paradigms, stakeholders' buy-in, infrastructure, and advances in technology), organizationrelated factors (culture, available resources, integration with existing processes, relationships, skill mix, and staff involvement), and individual professional factors (professional role, underlying philosophy of care, and competencies) (13). Contextualization involves designing and fitting the recommendations to the implementation environment and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Without targeted contextualized (13) and appropriately communicated guidelines, care providers, patients, policy makers, payers, and communities are not guided adequately on the best practices to yield better outcomes (13). Considerations for contextualization should include factors related to each of the stakeholders, including external contextual factors (policies, incentivization structures, dominant paradigms, stakeholders' buy-in, infrastructure, and advances in technology), organizationrelated factors (culture, available resources, integration with existing processes, relationships, skill mix, and staff involvement), and individual professional factors (professional role, underlying philosophy of care, and competencies) (13). Contextualization involves designing and fitting the recommendations to the implementation environment and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Target audiences were divided into providers, patients, populace, policy makers, implementation partners (e.g., professional bodies, advocates, relevant nongovernmental organizations, etc. ), and payers (entities other than patient that finance or reimburse the cost of health services) (13). A guideline was deemed to have complied with each IOM standard when all the stated IOM requirements were met (18).…”
Section: Data Itemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies (Loef & Walach 2012, van Dam et al 2008, Khaw et al 2008 showed that modern food production/distribution and increased industrialization of agro-food systems have influenced significantly the worldwide dietary habit and nutritional components of eating patterns with a strong impact on nutritional outcomes (Owolabi et al 2016, World Health Organization 2011, Hawkes 2006, Garnett et al 2013, Knight et al 2016. It is widely demonstrated that eating habit as a whole, rather than an individual nutrient or groups of them, interacts with health status (Schulze & Hu 2002, Jacques & Tucker 2001, Fung et al 2001) and may have a significant influence on modifiable risk factors of noncommunicable diseases (NCDs), which are reaching epidemic proportions worldwide.…”
Section: Introductionmentioning
confidence: 99%